Negative temperature coefficient of single-walled carbon nanotube-gold nanoparticle hybrid structures - N. Songmee (2018)
Single-walled carbon nanotubes (SWNTs) were grown on gold nanoparticle (GNP) coated quartz substrates by alcohol catalytic chemical vapor deposition. The GNP coated substrates were coated with Co catalyst by a dip-coat method. The growth was then carried out at 800°C under a pressure of 10 Torr in an atmosphere of ethanol vapor for 30 min. Characterizations have shown larger SWNT diameters with higher negative temperature coefficients for GNP coated substrates as compared to those of quartz substrates without GNPs. It is attributed that SWNT-GNP hybrid structures have a higher fraction of semiconductor-type pathways. Copyright © 2008 American Scientific Publishers All rights reserved.